ASISTENSI PENULISAN ARTIKEL ILMIAH DALAM PROGRAM PENUNJANG KARIR GURU: KUALITATIF-PARTISIPATORIS, GURU DANE INDONESIA - Hasan Basri; Muhammad Ali Sukran; Muh Fahrurrozi; Muhammad Ramli; Muhammad Adi Junaidi (LPPM Universitas Bina Bangsa, 2023)
The publication of scientific papers across fields of national and international standards is a measurable variability in academic units. Writing worthy of publication is a suitable measure met as a guarantee of teacher quality. Indicators of infertile writing motivations have implications for the number of articles published in the reputable indexer database. The practice of the scientific writing assistance program to teachers, prospective teachers, and lecturers aims to provide holistic debriefing of scientific writing knowledge. This scientific writing assistance activity adopts a qualitative-participatory approach by adopting a group-work discussion and quiz learning model. Learning activities are questions and answers as well as workshops. The population is a prospective teacher, teacher (junior and senior high school), and lecturer in Lombok Timur district with random sampling as the sampling technique. There were 18 participants selected from the google form through random screening. We found that the majority of participants had no experience writing scientific articles. Writing introductions, literature reviews, and discussions became the most severe problem of all the participants who participated in the training. On the contrary, participants had no constraints on the part of the findings, methods, and conclusions